Comparison of Lipid Profiles among Vegan Vegetarians, Lacto-Ovo Vegetarians and Non-Vegetarians - Sineri, Dessy Ikasartika; Nurwati, Ida; Sumardiyono, Sumardiyono (JURNAL INFO KESEHATAN, 2024)
The lipid profile is a crucial indicator of cardiovascular disease risk, with elevated levels often influenced by dietary patterns. Nutrient intake and physical activity can help regulate cholesterol by reducing total cholesterol, HDL, LDL and triglyceride levels. This study aims to compare the lipid profiles among vegan vegetarians, lacto-ovo vegetarians, and non-vegetarians. This research uses a cross-sectional study design. The study population includes 60 participants from IVS and the Yogyakarta community, selected based on inclusion and exclusion criteria. The research examines diet type as the independent variable, lipid profile as the dependent variable, and physical activity as a confounding variable. Data collection involves respondent identity and a physical activity questionnaire using IPAQ. Statistical analyses include one-way ANOVA, Post Hoc tests and multivariate analysis with one-way MANCOVA. The research results show that the total cholesterol level for vegan (173.10±21.04), lacto-ovo (169.45±44.84), and non-vegetarians (194.55±31.40). HDL levels for vegan are (55.25±10.79), lacto-ovo (49.00±9.12), and non-vegetarians (45.49±9.11). LDL levels for vegan are (111.90±19.80), lacto-ovo (114.85±44.39), and non-vegetarians (134.90±30.37), showing no significant difference p>0.05. Triglyceride levels for vegan are (103.15±57.06), lacto-ovo (100.65±60.07), and non-vegetarians (154.15±88.63) with significant differences p-value <0.05. When controlling for physical activity, differences in total cholesterol, HDL, and triglycerides persist between diet groups. Notably, HDL levels differ significantly between vegans and lacto-ovo (p<0.05). The conclusion is that both vegan and lacto-ovo diets have lipid profiles within the normal range compared to non-vegetarian diets. A vegetarian diet and regular physical activity contribute to a healthier lipid profile.